2012
DOI: 10.4269/ajtmh.2012.11-0263
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Indicators of Microbial Drinking Water Quality for Health Studies in Tropical Developing Countries: Case Study in Northern Coastal Ecuador

Abstract: Abstract. To address the problem of the health impacts of unsafe drinking water, methods are needed to assess microbiologic contamination in water. However, indicators of water quality have provided mixed results. We evaluate five assays (three for Escherichia coli and one each for enterococci and somatic coliphage) of microbial contamination in villages in rural Ecuador that rely mostly on untreated drinking water. Only membrane filtration for E. coli using mI agar detected a significant association with hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 22 publications
2
57
1
1
Order By: Relevance
“…18 These variable results between study sites are not unexpected given regional differences in the non-fecal contributions to microbial indicator levels and in the relative importance of drinking water as a disease transmission pathway. 19 Our observation of low child diarrhea prevalence despite poor microbial water quality suggests that although the ground water sources in the study region are exposed to environmental microbial contamination, basic protection from fecal contamination may be sufficient to prevent the majority of water source-transmitted disease risk. 34 The consistent increase in household-level microbial contamination (Figure 1), however, indicates that water contamination during storage remains a potential transmission pathway for pathogens that could facilitate rapid disease spread during a diarrheal disease outbreak.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…18 These variable results between study sites are not unexpected given regional differences in the non-fecal contributions to microbial indicator levels and in the relative importance of drinking water as a disease transmission pathway. 19 Our observation of low child diarrhea prevalence despite poor microbial water quality suggests that although the ground water sources in the study region are exposed to environmental microbial contamination, basic protection from fecal contamination may be sufficient to prevent the majority of water source-transmitted disease risk. 34 The consistent increase in household-level microbial contamination (Figure 1), however, indicates that water contamination during storage remains a potential transmission pathway for pathogens that could facilitate rapid disease spread during a diarrheal disease outbreak.…”
Section: Discussionmentioning
confidence: 98%
“…22,[38][39][40] In addition, culture-based assays for coliform species, particularly methods developed for field use, do not always produce comparable results. 19 It is likely that differences in the microbial ecology of water supplies and in the performance of coliform assays have both contributed to the variable associations reported between H 2 S and coliform test results. 22 Despite the challenges of evaluating H 2 S as a fecal indicator based solely on comparisons with coliform assays, our results show that in rural southern India, H 2 S was associated with higher levels of total coliform contamination ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research has shown an association between the consumption of highly contaminated water and diarrhea, 42,43 but other investigations have found no significant association between the level of fecal contamination in stored household drinking water and disease risk. [44][45][46][47] A recent systematic review and meta-analysis demonstrated an association between the detection-but not the amount-of E. coli contamination and diarrhea. 48 The considerable contamination of improved water sources observed in this and other studies demonstrates that the current MDG indicator for water quality should not be equated with safety.…”
Section: Discussionmentioning
confidence: 99%